Inovasi Komunikasi Pemasaran Indosat untuk Menarik Minat Generasi Z di Era Digital - Kurniati; Rina Pebriana (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to analyze the marketing communication strategies implemented by Indosat Ooredoo Hutchison in reaching Generation Z in the era of digitalization. Gen Z, as a consumer group that grew up in a digital technology environment, has different characteristics in receiving marketing information, thus requiring companies to develop creative, interactive, and digital-based communication approaches. This study uses a qualitative descriptive method with data collection techniques in the form of participatory observation, in-depth interviews, and documentation during an internship at Indosat. The results show that Indosat utilizes various digital channels such as social media, creative content-based campaigns, and collaborations with influencers to create marketing communications that are relevant to Gen Z's lifestyle. In addition, the strategy of strengthening brand identity through authentic messages that are in line with the values of the younger generation is an important aspect in increasing customer engagement and loyalty. Thus, Indosat's marketing communication strategy can be categorized as effective in building long-term relationships with Gen Z, especially through the use of digital media that is adaptive and responsive to changes in consumer behavior.